Difficile est saturam bene vertere : os desafios da tradução poética e uma versão brasileira das Sátiras de Juvenal - Carmo, Rafael Cavalcanti do (2018)
This study presents a translation of Decimus Junius Juvenal’s complete works, a latin poet whose work was written in the early second century A.D. Besides presenting a version of the juvenalian work to portuguese, the study proposes a panorama concerning the ideas of some authors who dedicated thoughts and commentaries about translation. Such panorama, besides informing about the ways in which translation has been understood in different periods, carries out the function of offering a complex of notions from which not only a specific procedure has been elected as a guide to the translating effort here attempted, but also an understanding concerning translation has been solidified, of which this study is illustrative. Furthermore, the study aimed to make brief comments about former translations of Juvenal’s work: those made by Francisco António Martins Bastos and António de Sousa da Silva Costa Lobo, translator of the nineteenth century, as well as about the translation in which this very work consists, aiming to illustrate the relevancy of personal reading and interpretation to the final result of a given translation. Thus the work highlights the intimate relation that the translator’s activity has with that of the critic.